Single-Cell RNA Sequencing Analysis of Steroidogenesis and Spermatogenesis Impairment in the Testis of db/db Mice - Yun Hu; Ting-Ting Cai; Reng-Na Yan; Bing-Li Liu; Bo Ding; Jian-Hua Ma (International Journal of Endocrinology)
Objective. The mechanism of steroidogenesis and spermatogenesis impairment in men with type 2 diabetes remains unclear. We aimed to explore the local changes of steroidogenesis and spermatogenesis in the testis of db/db mice. Research Design and Methods. We performed single-cell RNA sequencing analysis in the testis of db/db and C57BL/6J mice. The differentially expressed genes were then confirmed by real-time PCR. The histopathological characteristics of testis in db/db mice and C57BL/6J control were also performed. Results. The 20-week-old db/db mice had significantly higher blood glucose and body weight (both p<0.001). The serum testosterone levels (4.4 ± 0.8 vs. 9.8 ± 0.7 ng/ml, p=0.001) and weight of the testis (0.16 ± 0.01 vs. 0.24 ± 0.01 g, p<0.001) were significantly lower in db/db mice than that in C57BL/6J controls. db/db mice had a lower cross-sectional area of seminiferous tubules and thickness of the cell layer (both p<0.05). The numbers of Sertoli cells and Leydig cells decreased in db/db mice (both p<0.01). Single-cell RNA sequencing analysis showed that compared with the control group, the percentage of spermatogonia was significantly higher in the db/db mouse (p<0.001), while the proportions of spermatocytes, round and elongating spermatids, and sperms were all lower in the db/db mouse (p all<0.001). The most differentially expressed genes were found in round spermatids (n = 86), which were not found in spermatogonia, spermatocyte, and sperm. Igfbp5 was the most significantly decreased gene in Leydig cells of the db/db mouse, while the expression of Cd74, H2-Aa, and H2-Eb1 was elevated. Ccl7 and Ptgds were the most significantly increased and decreased genes in Sertoli cells of the db/db mouse. Conclusions. The present study indicates spermiogenesis and steroidogenesis defects in db/db mice. The mechanism of steroidogenesis impairment in the testis of db/db mice deserves further investigation.